Tasks proposed by prospective teachers of the first school years to teach probability - Fernandes, José António (2019)
Recently we have witnessed the deepening of the teaching of Probability and Statistics in basic education, where it is important to investigate if the knowledge of prospective teachers is adequate to teach these subjects. 53 students, who were attending the 2nd year of the Bachelor's Degree in Basic Education at a university in Portugal, were asked to solve various questions on probability. We study only the one that refers to the didactic dimension of the prospective teacher's knowledge, when they establish tasks of probability suitable for students of the primary education. In the results obtained, it was found that the majority of participants presented inappropriate tasks to the cognitive level of the students for whom they were intended, and they were generally too difficult and without reference to uncertainty. The tasks were very similar to the learning that the prospective teachers themselves have done under the topic of probability in their previous training.